The risk of radiation necrosis from combined radiotherapy and BRAF inhibitor in lung adenocarcinoma brain metastases: a comprehensive review and future perspectives - Yang, Lina; He, Yanan; Peng, Yong; Sun, Mao; Tang, Zheng; Du, Liang; Wu, Yongzhong; Zhou, Wei; Yang, Dingyi (Frontiers in Oncology, 2026)
The management of lung adenocarcinoma with brain metastases (BMs) is particularly challenging when BRAF-V600E mutations emerge as a resistance mechanism to EGFR tyrosine kinase inhibitors. While the combination of BRAF/MEK inhibitors (e.g., dabrafenib and trametinib) and radiotherapy (RT) is a pivotal therapeutic strategy, it significantly increases the risk of radiation necrosis (RN). This review summarizes the current understanding of the molecular mechanisms and risk factors underlying RN development in this specific patient population. We detail how BRAFi exacerbate RT-induced vascular injury, blood-brain barrier (BBB) disruption, and inflammatory responses, focusing on MAPK pathway modulation, VEGF signaling inhibition, and paradoxical pathway activation. Clinical correlations regarding treatment timing and regimen choice are discussed. Finally, we propose comprehensive strategies to mitigate RN risk, including optimized treatment sequencing, RT dose adjustments, advanced imaging for early detection, and novel approaches for vascular repair. This review underscores prospective studies and standardized guidelines are urgently needed to refine combination strategies and improve outcomes for these patients.